2022
DOI: 10.1108/ijdi-09-2022-0208
|View full text |Cite
|
Sign up to set email alerts
|

Trade misinvoicing and domestic resource mobilization in Nigeria

Abstract: Purpose Mobilizing domestic resources has been a daunting task for the Nigerian government given its growing fiscal responsibilities and the limited domestic resources at its disposal. However, little is known empirically about the role trade misinvoicing plays in this regard. Hence, this study evaluates the effect of trade misinvoicing on domestic resource mobilization in Nigeria. Design/methodology/approach Sourcing annual data spanning 1981–2018 on key variables of interest, this study adopts the Dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The amount of financial resources leaving the confines of SSA partly explains the region’s slow economic progress. This result corroborates earlier findings such as Afolabi (2022a, 2023), which showed that trade misinvoicing adversely affect economic growth through the government revenue and domestic investment channels. Similarly, it parallels the view of Podder (2022), who argued that trade misinvoicing has corrosive effects on macroeconomic performance as it reduces government revenue base, lowers foreign exchange earnings, depletes external reserve and, ultimately, stifle economic growth.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The amount of financial resources leaving the confines of SSA partly explains the region’s slow economic progress. This result corroborates earlier findings such as Afolabi (2022a, 2023), which showed that trade misinvoicing adversely affect economic growth through the government revenue and domestic investment channels. Similarly, it parallels the view of Podder (2022), who argued that trade misinvoicing has corrosive effects on macroeconomic performance as it reduces government revenue base, lowers foreign exchange earnings, depletes external reserve and, ultimately, stifle economic growth.…”
Section: Resultssupporting
confidence: 92%
“…Onogwu (2019), who used 2005-2014 to analyse the development effect of IFFs, also found that IFFs drain the limited potential development funds in Nigeria. Afolabi (2023) supported this notion by showing that trade misinvoicing hampers domestic resource mobilisation and attenuates Nigeria's economic growth. Mwaura and Olweny (2020) also examined the growth effect of IFFs in Kenya for the period covering 2013-2018.…”
Section: Brief Review Of Related Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…However, having met the pre-conditions for digitalisation to mitigate the impact of corruption on DRM, the existence of a turning point cannot be disregarded. To address this, the point at which the impact of digitalisation dominates and becomes positive was calculated using equation (6). Although somewhat simplistic, the proposed approach involves solving for 𝑙𝑛𝐷𝑖𝑔 ̅̅̅̅̅̅̅̅ as outlined below:…”
Section: Turning Pointmentioning
confidence: 99%
“…On the other hand, given the low revenue base of the Nigeria government, the government has been compelled to increase the country's debt stock to finance its rising military expenditure and annual budget. Thus, Nigeria's debt profile (debt from both domestic and international creditors) together with its associated cost of debt servicing poses critical threats to domestic resource mobilization for investment and growth imperatives (Onyele and Nwadike, 2021;Afolabi, 2022aAfolabi, , 2023.…”
Section: Introductionmentioning
confidence: 99%